Hadith #3909 - Sunan Abi Dawud - ibn Mas'ud; Isa bin 'Asim al-Asady عيسى بن عاصم الأسدي الكوفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Sunan Abi Dawud)
I said: Messenger of Allah! among us there are men who practice divination by drawing lines. He said: There was a Prophet who drew lines, so if anyone does it as he drew lines, that is right.
Grade: Sahih